Rethinking Schizophrenia in the Context of the Person and Their Circumstances: Seven Reasons - Pérez-Álvarez, Marino; García-Montes, José M.; Vallina-Fernández, Oscar; Perona-Garcelán, Salvador (Frontiers in Psychology, 2016)
We know a great deal about schizophrenia, but the current state of the art is one of uncertainty. Researchers are confused, and patients feel misunderstood. This situation has been identified as due largely to the fact that the dominant neurobiological perspective leaves out the person. The aim of the present article is to review and integrate a series of clinical, phenomenological, historical, cultural, epidemiological, developmental, epigenetic and therapeutic phenomena in support of a suggestion that schizophrenia is above all a disorder of the person rather than of the brain. Specifically, we review seven phenomena, beginning with the conception of schizophrenia as a particular disorder of the self. We continue by looking at its recent origin, as a modern phenomenon, its juvenile onset, related to the formation of the self, the better prognosis in developing countries compared to developed countries, and the high incidence of the disorder among migrants. In the context of these phenomena of a marked socio-cultural nature, we consider the so-called “genetic myth”, according to which schizophrenia would have a genetic origin. On reviewing the current genetic emphasis in the light of epigenetics, it emerges that the environment and behaviour recover their prominent role in the vicissitudes of development. The seventh reason, which closes the circle of the argument, concerns the role of interpersonal “chemistry” in recovery of the sense of self.